Antimony induced structural and ultrastructural changes in Trapa natans - Sangita Baruah (Nature Portfolio, 2021)
Abstract Antimony (Sb) is considered as a priority toxic metalloid in the earth crust having no known biological function. The current study was carried out in a hydroponic experiment to study the accumulation of ecotoxic Sb in subcellular level, and to find out the ultrastructural damage caused by Sb in different vegetative parts of Trapa natans. Sb-induced structural and ultrastructural changes of T. natans were investigated using scanning electron microscope (SEM) and transmission electron microscope (TEM). Experimental plants were exposed to different Sb(III) treatments: SbT1 (1.5 μmol/L), SbT2 (40 μmol/L) and SbT3 (60 μmol/L). Calculated bioconcentration factor (BCF) and translocation factor (TF) showed that at higher concentration (SbT2, SbT3), T. natans is a potent phytoexcluder whereas it can translocate a substantial amount of Sb to the aerial parts at lower concentration (SbT1). SEM analysis revealed Sb-mediated structural changes in the size of stomatal aperture, intercellular spaces and vascular bundles of different vegetative tissues of T. natans. TEM results showed subcellular compartmentalization of Sb in vacuole and cell wall as electron dense deposition. This is considered as a part of strategy of T. natans to detoxify the deleterious effects under Sb stress conditions. Fourier transform infrared spectroscopy (FTIR) study of plant biomass revealed possible metabolites of T. natans which can bind Sb.